PECULIARITIES OF POSTCATASTROPHIC PYROGENIC DYNAMICS OF THE LIVING GROUND COVER IN THE FOREST-STEPPE PINE PHYTOCOENOSIS OF UKRAINE - Voron, V. P.; Melnik, E. E. (Forestry and Forest Melioration, 2018)
Introduction Forest fires are environmental factors that lead to significant adverse changes in forest ecosystems. An essential indicator of their pyrogenic transformation is a change in living ground cover. Studies of fires impact on Ukrainian forests concern stands in general, and changes in the living ground cover are virtually unknown. Materials and Methods Research of pyrogenic transformation of pine plantations was held for six years by 9 permanent sample plots established in pure middle-aged pine forests with similar forest conditions (fresh fairly infertile pine site type) in the State Enterprise “Zmiyivske Forest Economy” which is located in the south-eastern part of the Left-bank Forest-Steppe. For the first time for this territory, the pyrogenic changes in species composition, ecomorphic and biomorphic structure of the living ground cover have been investigated. Results and Conclusions After the fire, the state of stands had continued to deteriorate during the observation time. Living ground cover consisting of forest species was almost completely destroyed by fire. Mossy vegetation had completely disappeared from it. Hylocomium splendens, which projective cover amounts up to 37 % in the control plot, has not restored even 6 years after the fire. On the fourth and subsequent years after the fire, there was a significant sod formation due to the spread of cereals. Calamagrostis epigeios (L.) Roth. dominates among them. In the fourth year after the fire, its projective cover reached 20–32 %, and after 6 years, 52 %. On the second and the third year after fires, perennial species (Poa sylvicola (L.) Guss., Taraxacum officinale (L.) Weber ex F.H. Wigg, Chelidonium majus L., Carex pilosa Scop.) are dominated in the forest floor (52.1–63.6%); nevertheless, the projective cover of annual plants reaches 44.7 %, largely due to the ruderant Erigeron canadensis L. The share of annual plants is further reduced (up to 25–38 %), and of perennial ones increased (up to 65–72%) In the early years after a fire, there is a significant spread of field weeds and meadow species on the forest floor. On the fourth year and in the future the share of the weeds is reduced and it is increased for meadow species. The share of forest species ranges from 7.8 to 21.5 % up to the fifth year, and only on the sixth year, it rises to 30.8 %. The species appear in shaded areas generally.